2020
DOI: 10.34074/scop.6001010
|View full text |Cite
|
Sign up to set email alerts
|

Communities of Practice for Independent Learning Practitioners at Capable NZ, Otago Polytechnic

Abstract: This paper explores a range of face-to-face and online communities of practice (CoP) that are used to support groups of learners or mentors at degree and diploma levels using Independent Learning Programmes at Otago Polytechnic's Capable NZ. The six writers each create a narrative linking the purpose of specific CoPs to their observable outcomes. The narratives demonstrate such CoP features as mutual engagement, joint enterprise and shared repertoire. The value of the CoPs, over and above uniting colleagues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…This approach recognises Mason Durie's (1998) Te Whare Tapa Whā model of Māori health which includes the spiritual, the mental/emotional, the physical and the social aspects of every participant's life. CoPs provide a richness and exchange that raises the repertoire of the entire group as explored in a series of narratives (Henry et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach recognises Mason Durie's (1998) Te Whare Tapa Whā model of Māori health which includes the spiritual, the mental/emotional, the physical and the social aspects of every participant's life. CoPs provide a richness and exchange that raises the repertoire of the entire group as explored in a series of narratives (Henry et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Meeting the responsibilities inherent in these values was a major undertaking, so I adopted a whakatauk ī (Māori proverb) to guide me through the degustation project: "Whāia te iti kahurangi ki te tūohu koe me he maunga teitei" (Woodward, 2020): "Seek the treasure you value most dearly and if you bow your head, let it be to a lofty mountain." The message of this whakatauk ī is to be persistent and not to let obstacles stop you from reaching your goal.…”
Section: The Matariki Celebrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020 we investigated key evidence-based (Cullen et al, 2017) theories and models that link to teaching practice (Woodward et al, 2020) and then considered constructivism and reflective practice as an evidence-based approach to tertiary teaching (Woodward et al, 2021). Henry et al (2020) have identified communities of practice as an effective social constructivist tool for building trust and a sense of belonging, sharing of enterprise and enhancing the reflectivity that is a precursor to independent learning. We therefore employed this social constructivist (Palincsar, 1998) approach to mine information from interviewees, all OP lecturers or facilitators, using an autoethnographic (Maréchal, 2010) approach involving reflection on teaching experience.…”
Section: Methodsmentioning
confidence: 99%
“…It is important that educators are scaffolded into tertiary teaching, in manageable steps, using a supportive secondary teaching model and a constructivist approach of learning by doing and reflection, supported in a community of practice of like-minded, experienced educators (Henry et al, 2020) to bounce ideas off -rather than a traditional approach that represents outdated assumptions about the teacher's identity, ability and role.…”
Section: Recommendationsmentioning
confidence: 99%